2019
DOI: 10.1051/epjconf/201922101053
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the stress-strain state of a coal seam caused by an explosion of a blast-hole charge with an annular gap

Abstract: The computer simulation of the propagation of a blast wave generated by various explosives is carried out. The simulation used numerical methods to solve dynamic problems in the mechanics of a deformable solid, which allow one to investigate the development of waves during the explosion of charges of various shapes at different speeds of detonation of explosives and various conditions of placement of charges in the hole. The novelty of the research is related to analysis of conditions for the formation of a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Взрывную деформацию, разрушение пласта и его дегазацию следует рассматривать как единый взаимосвязанный процесс. С этой целью в работе используется объединенная модель газонасыщенного угольного пласта для описания иерархической взаимосвязи между взрывным повреждением угольного пласта и газовыделением [1,2]. На основе этой модели с помощью численного моделирования исследуется развитие зоны разрушений и определяется напряженно-деформированное состояние пласта вблизи забоя до и после взрыва.…”
Section: институт проблем комплексного освоения недр им академика нunclassified
“…Взрывную деформацию, разрушение пласта и его дегазацию следует рассматривать как единый взаимосвязанный процесс. С этой целью в работе используется объединенная модель газонасыщенного угольного пласта для описания иерархической взаимосвязи между взрывным повреждением угольного пласта и газовыделением [1,2]. На основе этой модели с помощью численного моделирования исследуется развитие зоны разрушений и определяется напряженно-деформированное состояние пласта вблизи забоя до и после взрыва.…”
Section: институт проблем комплексного освоения недр им академика нunclassified
“…Ti et al [10] conducted research based on the Tingnan Coal Mine, a numerical model of blasting coal with different blasthole spacing was established, and the effect of blasthole spacing on coal crack propagation was studied. Iwan Shipovskii1 et al [11] conducted simulations to examine how blasting rates affected the growth of coal cracks. It was found that the crack growth of coal was closely related to the blasting speed, and had nothing to do with the design of explosives.…”
Section: Introductionmentioning
confidence: 99%